Research Progress of Deep Eutectic Solvents in the Recycling of Spent Lithium-ion Batteries - Xiaoxue MA; Haifeng WANG; Jiawei WANG; Zihui ZHANG; Juan HAO; Yaqun HE (Kuangchan zonghe liyong)
With the rapid development of electric vehicles, energy storage and other industries, the demand for lithium-ion batteries is growing rapidly, and the amount of their disposal is also increasing, and the efficient resource recovery of spent lithium-ion batteries has become a major problem that needs to be solved in China. The current methods of pyrometallurgy, hydrometallurgy and repair and regeneration of spent lithium-ion batteries have their own shortcomings, and there is an urgent need for greener and more efficient recycling and treatment methods. Deep eutectic solvents have unique advantages in the recycling of spent lithium-ion batteries due to their thermal stability, easy synthesis and low toxicity. In this paper, the research progress of deep eutectic solvents in leaching, dissociation and repair and regeneration of cathode materials of spent lithium-ion batteries is introduced in detail, the leaching mechanism of valuable metals is elaborated, and finally the development trend of deepeutectic solvents in the resource recycling of spent lithium-ion batteries is anticipated.